Pulmonary toxic responses to intraperitoneal administration of nickel nanoparticles in male rats - Abdulqadir, Shang Z. (Zanco Journal of Pure and Applied Sciences, 2025)
The harmful effects of different levels of Nickel nanoparticles (Ni-NPs) (particle size = 20nm) on male rats' lungs were explored in the study. Intraperitoneal injection of Ni-NPs occurred at 0, 5, 20, and 100mg/kg/bw over 28 days. The quantity of malondialdehyde (MDA). The evaluation also included the levels of reduced glutathione (GSH) and the activity of antioxidant enzymes, including superoxide dismutase (SOD), glutathione peroxidase (GPX), and catalase (CAT). Additionally, observations were made on lung changes at the histopathological, immunological, and ultrastructural levels. Lung homogenates displayed a noticeable increase in MDA levels, which was dependent on the dosage. Dose-dependent changes were observed in the biochemical parameters. Histological analysis revealed several abnormalities in the rats treated with Ni-NPs, including thickening of alveolar walls. Pulmonary vessels experience blood congestion, lung parenchyma is severely damaged, and lung tissues suffer from hemorrhage. The diffuse appearance of the inflammatory leukocytes stood out as the most evident histopathological characteristic. A dose-dependent pattern was observed in all of these histopathological features. The p53 immunohistochemical demonstration exhibited a higher reaction intensity compared to the control. Examination of the ultrastructure showed that exposure to Ni-NPs led to damage in the mitochondria. The detected biochemical, histological, immunohistochemical, and ultrastructural alterations in the rat lungs demonstrate the harmful effects of NiNPs on lung health. These effects seem to be mediated in large part by the production of oxidative stress.